Integration of Islamic Values in Social Arithmetic Learning: A Systematic Review Study - St. Sulastri; Baharullah; Mukhlis (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2025)
In fact, most educators in schools or madrasahs admit that they face challenges when integrating mathematics with Islam. Therefore, this study aims to investigate the concept of integrating Islamic values ​​into mathematics learning, with a special emphasis on social arithmetic material. This research method uses a systematic review of the results of recent research (updates) over the past five years. The results of the study indicate that the integration or combination of mathematics learning with Islamic values ​​can be a method of instilling Islamic values. Therefore, we anticipate that instilling Islamic values ​​will not only improve the application of mathematics in students' daily lives but also increase their faith and piety. All educators, including mathematics instructors, can bear the responsibility to instill religious values. Therefore, we anticipate that by incorporating Islamic values ​​into mathematics learning that are in line with the subject matter, mathematics educators will be able to foster students' character. Consequently, the findings of this study will significantly enhance the domain of mathematics education by elevating the quality of learning through a method that incorporates Islamic values. We recommend that additional academics examine the correlation between students' learning outcomes or motivation and mathematical problems that incorporate Islamic values.